(untitled) (Research, Society and Development, 2024)
The consumption of cooking oil is part of the daily lives of families, restaurants, cafeterias, industries in general and the incorrect disposal of used cooking oil (OCU) becomes an increasingly serious environmental problem. Searching for solutions for the reuse of this waste becomes extremely relevant, where through reverse logistics it becomes an option for creating new possibilities such as transforming used oil into biodiesel. The objective of this study is to promote environmental issues as well as encourage the subject through the application of reverse logistics. Correct disposal contributes to combating pollution and maintaining natural resources. The methodologies applied were action research, descriptive and case study, where the results were favorable to the manufacture of biodiesel from the residue generated by cooking oil. In turn, the study contributes to the understanding of the effectiveness of adopting environmental sustainability measures through the reuse of waste, in particular, the adoption of models such as reverse logistics, which may therefore be of practical applicability.